Case Report: Double Micro-Guidewire Technique for Emergent Rescue of Proximal Stent Collapse During Recanalization of Nonacute Occlusion of Vertebral Artery - Zhang, Kun; Xia, Jin-Chao; Gao, Hui-Li; Gao, Bu-Lang; Wang, Yong-Feng; Li, Zhao-Shuo; Li, Tian-Xiao; Wang, Zi-Liang (Frontiers in Neurology, 2021)
Cerebral arteries are usually tortuous, and in the treatment of cerebrovascular diseases with stenting, a stent deployed may be collapsed at one end, leading to reduced blood flow and subsequent stent occlusion. Immediate rescuing measures should be implemented to prevent severe ischemic events. In this case report, we present a case with V4 segment occlusion of the right vertebral artery treated with endovascular stent angioplasty. An Enterprise stent deployed at the occlusion segment was collapsed at the proximal end after withdrawal of the delivery system. Immediate rescuing measures were taken by navigating a micro-guidewire through the lateral stent mesh at the proximal end into the stent lumen followed by advancing a second micro-guidewire right through the reopened proximal stent end into the stent lumen for deployment of a supporting balloon-expandable Apollo stent to prevent stent collapse. Follow-up digital subtraction angiography 6 months later demonstrated patent stents and unobstructed blood flow.